Perjanjian Yang Dilakukan Oleh Orang Dengan Kepribadian Ganda (Dissosiative Identitiy Disorder) Ditinjau Dari Hukum Perjanjian - Cindya Sephia Putri (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Agreements are a fundamental aspect carried out by humans as social creatures. Human conditions are not always the same where there are people with certain conditions both physically and mentally. Humans are individual subjects who have equal rights and obligations under the law. However, several factors influence human rights and obligations, such as mental illness. Dissociative Identity Disorder (dual personality) is a mental illness that affects human consciousness. There is an urgency for sufferers of Dissociative Identity Disorder in legal actions such as carrying out contractual activities. Full awareness is required when agreeing, whereas sufferers of dissociative identity disorder have problems with their awareness if the disease recurs. There is a need for a legal study of contractual actions carried out by sufferers of dissociative identity disorder because this will affect the validity of the agreement. This type of research is normative research with a literature study that includes laws. This research further clarifies the status of agreements entered into by people with dissociative identity disorder and the legal consequences. The solution offered is also urgent considering that the problems faced have not been widely discussed, so it becomes urgent for the agreement status of people with dissociative identity disorder.